Algorithms for the management of patients with anxiety in the internist’s practice - V. N. Shishkova; Yu. G. Dranitsyna; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The development of guidelines for the detection and further management of patients with anxiety for outpatient physicians is relevant due to the high incidence of anxiety disorders in patients with non-communicable diseases, including cardiovascular diseases, deterioration in quality of life and an increase in adverse outcomes in patients with anxiety. In addition, there is an insufficient awareness of outpatient doctors about the importance of diagnosing and treating anxiety disorders. The aim was to present original "Algorithms for the Management of Patients with Anxiety in the Internist’s Practice" for the detection and timely treatment of anxiety disorders in the routine practice of an internal medicine doctor. The algorithms are intended for internal medicine specialists working in primary outpatient healthcare, as well as for residents.